Penggunaan Agregat Kasar Tondon Marante Untuk Campuran HRS-BASE dan Campuran AC-BC - Israel Padang (Journal Dynamic Saint, 2020)
The availability of road construction materials matching the design criteria and mixed features in terms of reliability is one of the success factors in road construction. The goal of this study is to understand whether Tondon Marante coarse aggregate in Hot Rolled Sheet Binder-Course mix and in Asphalt Concrete Binder-Course mixture can be used as flexible pavement road material. This study was carried out by measuring the characteristic of Marshal using penetration asphalt 60/70 for Hot Rolled Sheet Binder-Course mixture on asphalt content variation of 6 percent, 6.5 percent, 7 percent, 7.5 percent, 8 percent and for Asphalt Concrete Binder-Course mixture on bitumen content variation of 5 percent, 5.5 percent, 6.5 percent, 6.5 percent, 7 percent according to Asphalt Concrete Binder-Course mixture on bitumen content variation. The results showed that Hot Rolled Sheet Binder-Course mixture's optimum asphalt content was 7 percent with a VIM value of 4.78 percent, VFB 74.32 percent, VMA 18.37 percent, Stability 894.83 kg, Flow 3.32 mm, MQ 269.22 kg / mm and 24 hours immersion index 94.05 percent, and Asphalt Concrete Binder-Course mixture's optimum asphalt content is 6.5 percent with a VIM value of 3.83 percent. It is concluded that Tondon Marante coarse aggregate can be used as a versatile pavement road material in a mixture of Hot Rolled Sheet Binder-Course and Asphalt Concrete Binder-Course mix, based on the Marshal characteristic test that primarily meets the general specification of Bina Marga 2010 Revision 3 (Division 6) 'Asphalt Pavement'.